Barriers to the Implementation of Newborn Pulse Oximetry Screening: A Different Perspective - Martin Kluckow (MDPI AG, 2018)
Pulse oximetry screening of the well newborn to assist in the diagnosis of critical congenital heart disease (CCHD) is increasingly being adopted. There are advantages to diagnosing CCHD prior to collapse, particularly if this occurs outside of the hospital setting. The current recommended approach links pulse oximetry screening with the assessment for CCHD. An alternative approach is to document the oxygen saturation as part of a routine set of vital signs in each newborn infant prior to discharge, delinking the measurement of oxygen saturation from assessment for CCHD. This approach, the way that many hospitals which contribute to the Australian New Zealand Neonatal Network (ANZNN) have introduced screening, has the potential benefits of decreasing parental anxiety and expectation, not requiring specific consent, changing the interpretation of false positives and therefore the timing of the test, and removing the pressure to perform an immediate echocardiogram if the test is positive. There are advantages of introducing a formal screening program, including the attainment of adequate funding and a universal approach, but the barriers noted above need to be dealt with and the process of acceptance by a national body as a screening test can take many years.